The Influence of Customer Relationship Management on Customer Interest in Depositing Money at Bank Syariah Indonesia Riau with the Moderating Variable of Public Trust Level - Muhammad Syarofi (UIN Raden Mas Said Surakarta, 2026)
The decline in deposit growth within Islamic banks has raised concerns about customer loyalty and relationship management effectiveness. This study aims to examine the influence of Customer Relationship Management (CRM) on customer intention to deposit money at Bank Syariah Indonesia (BSI) Riau, with public trust as a moderating variable. A quantitative survey method was employed, involving 210 respondents who are active or potential deposit customers of BSI. Data were collected using a structured questionnaire and analyzed through Structural Equation Modeling (SEM) using SmartPLS 4. The results reveal that CRM has a significant positive effect on customers’ deposit intentions (β = 0.48, p < 0.001), while public trust also exerts a positive influence (β = 0.29, p < 0.01). Furthermore, public trust moderates the relationship between CRM and deposit intention (β = 0.21, p < 0.05), indicating that trust enhances the effectiveness of CRM strategies. The novelty of this research lies in integrating public trust as a moderating factor in the relationship between CRM and deposit intention within the Islamic banking context. The study recommends that BSI strengthen its CRM through transparent communication, ethical service delivery, and digital engagement to foster customer trust and sustain deposit growth.